2019
DOI: 10.1186/s13568-019-0796-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of five bacterial strains producing siderophores with ability to chelate iron under alkaline conditions

Abstract: Iron deficiency is one of the main causes of chlorosis in plants, which leads to losses in field crops quality and yield. The use of synthetic chelates to prevent or correct iron-deficiency is not satisfactory mainly due to their poor biodegradability. The present work aimed to search suitable microorganisms to produce alternative, environment-friendly iron-chelating agents (siderophores). For this purpose, the performance of five bacteria ( Azotobacter vinelandii , Bacillus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(83 citation statements)
references
References 51 publications
4
78
0
1
Order By: Relevance
“…PSMs also release siderophores as a strategy to chelate iron from Fe-P complexes in the soil (Collavino et al 2010), although its role in phosphate dissolution needs to be further investigated. It was reported that under alkaline conditions, several phosphate solubilizers like Bacillus megaterium, Bacillus subtilis, Rhizobium radiobacter, and Pantoea allii produced siderophores in the range of 80 to 140 μmol L − 1 , which encouraged the survival of organisms under stress environment and also improved phosphorus solubilization (Ferreira et al 2019). Toscano-Verduzco et al (2020) found that novel fungi Beauveria brongniartii secreted siderophores, i.e., 59.8% of Fe 3+ -Chrome azurol-S degradation, and solubilized 158.95 mg L − 1 phosphorus in vitro.…”
Section: Siderophore Productionmentioning
confidence: 99%
“…PSMs also release siderophores as a strategy to chelate iron from Fe-P complexes in the soil (Collavino et al 2010), although its role in phosphate dissolution needs to be further investigated. It was reported that under alkaline conditions, several phosphate solubilizers like Bacillus megaterium, Bacillus subtilis, Rhizobium radiobacter, and Pantoea allii produced siderophores in the range of 80 to 140 μmol L − 1 , which encouraged the survival of organisms under stress environment and also improved phosphorus solubilization (Ferreira et al 2019). Toscano-Verduzco et al (2020) found that novel fungi Beauveria brongniartii secreted siderophores, i.e., 59.8% of Fe 3+ -Chrome azurol-S degradation, and solubilized 158.95 mg L − 1 phosphorus in vitro.…”
Section: Siderophore Productionmentioning
confidence: 99%
“…The ability of siderophore production is an important strategy employed by some PGPB to influence the plant growth by binding to the available form of Fe under Fe-limiting conditions (Ferreira et al 2019) which significantly reduces the quality and quantity of crop production. Among the evaluated isolates, KUU32 (B. subtilis), KHU53 (B. paralicheniformis), ALB32 (P. putida), and QAZ26 (S. maltophilia) presented the ability of siderophore production.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial filtrates were produced as described elsewhere (Ferreira et al, 2019b). Shortly, bacteria were grown in Fe-depleted media until siderophore concentration was stable (72 and 48 h for A. vinelandii and B subtilis , respectively).…”
Section: Methodsmentioning
confidence: 99%
“…To study the suitability of each bacterial media for Fe chlorosis remediation in soil applications, an Fe-siderophore solution (ISS) was prepared by rehydrating to the same volume the previously obtained powders; this procedure allowed to achieve the same initial concentration of siderophores. Then, a soluble salt of Fe(III), FeCl 3 .6H 2 O (Sigma), was added to the maximum complexation capacity at pH 9.0 ( A. vinelandii ≈ 188 µmol L −1 and B. subtilis ≈ 225 µmol L −1 ) of each solution, which was previously determined (Ferreira et al, 2019b). During the process, the pH of the solution was kept between 7.0 and 9.0, and the final pH was set at 9.0.…”
Section: Methodsmentioning
confidence: 99%